IMPLEMENTING BLENDED LEARNING IN THERMODYNAMICS MATERIALS TO GRADE XI SENIOR HIGH SCHOOL 16 SURABAYA - NURILLAH LAILATURIDLOH, FATICHATUL; SUNARTI, TITIN (Inovasi Pendidikan Fisika, 2018)
Blended Learning (BL) is popular and innovative learning in 21st Century and it is believed to decrease the portion of face-to-face instruction in Inquiry and Problem Based Learning (PBL). BL is learning activity that integrate several learning approaches, learning models and learning media. This research aimed to describe the implementation of Blended Learning in Thermodynamics materials to grade XI Senior High School 16 Surabaya. The type of this research is descrptive quantitative. The sample are XI-MIA 1 and XI MIA-2 and it is determained by using random sampling technique. The implementation of Blended Learning is observed by two observers using instructional learning sheet. The score is calculated from the average score of two observers in each class. The implementation of the online class is describe the students activity in Quipper School. The results of the implementation of first meeting with Cooperative learning using JIGSAW is 94% in the class experiment 1 and 93% in the class experiment 2. The second meeting with Inquiry using BL method is 93% for each class. The third meeting with Problem Based Learning using BL method is 90% in the class experiment 1 and 91% in the class experiment 2. The student activity in the online classroom using Quipper School is implemented well and it reinforce for this instruction. Keywords: Implementing Blended Learning, Quipper School.